Beyond methodological nationalism in insider research with migrants. (18th November 2013) - Nowicka, Magdalena; Cieslik, Anna
Abstract: This article outlines the key challenges that face those researchers who study migrants and are migrants themselves. We discuss how critics of methodological nationalism have proposed a new research programme in migration studies, which centres on a critique of the naturalization of nation and ethnicity, and the insufficient consideration of territoriality. This literature is put in conversation with studies on 'insider research', which offer similar suggestions for the epistemology and methodology of migration studies. We suggest that these two streams of debate can be enriched by adopting Ulrich Beck's concept of 'categorical consonance'. Finally, we discuss how, by a mean of comparison between different research sites and groups, the researchers dismiss categories of commonality that are grounded in methodological nationalism.